Media Lokal Ekonomis Untuk Kultivasi Trichophyton Rubrum: Inovasi Kacang Hijau, Glukosa Dan Kitin - Aima Insana; Siti Rachmah; Ricko Dharmadi Utama (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study examined the effect of modified mung bean powder (Vigna radiata) media with the addition of glucose and chitin on the growth of Trichophyton rubrum. The results of the One Way ANOVA test showed a p value = 0.931 (p>0.05), indicating no significant difference between the modified media and Sabouraud Dextrose Agar (SDA). Media with a concentration of 2% showed a colony diameter of 97.8% of the control, proving the ability of mung bean nutrition, glucose, and chitin to support fungal growth. The color of the media varied from light to dark yellow without affecting the morphology of the colony. The best growth occurred on the 4th to 14th day with a cotton-like colony texture. These results confirm the potential of modified mung bean media as an economical, environmentally friendly, and effective alternative to SDA, especially for laboratories with limited resources, as well as opening opportunities for the development of local media based on other natural materials.